2017
DOI: 10.1214/17-ejp24
|View full text |Cite
|
Sign up to set email alerts
|

Double roots of random polynomials with integer coefficients

Abstract: We consider random polynomials whose coefficients are independent and identically distributed on the integers. We prove that if the coefficient distribution has bounded support and its probability to take any particular value is at most $\tfrac12$, then the probability of the polynomial to have a double root is dominated by the probability that either $0$, $1$, or $-1$ is a double root up to an error of $o(n^{-2})$. We also show that if the support of coefficient distribution excludes $0$ then the double root … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…With the parameters α, β, δ, τ, R chosen as in Corollary 5.2, consider a non-exceptional polynomial P n . Let g be a trigonometric polynomial with g 2 ≤ τ , where τ is chosen as in (12). Consider a stable interval I j with respect to P n (there are at least ( 2π R − δ)n such intervals).…”
Section: Proof Of the Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the parameters α, β, δ, τ, R chosen as in Corollary 5.2, consider a non-exceptional polynomial P n . Let g be a trigonometric polynomial with g 2 ≤ τ , where τ is chosen as in (12). Consider a stable interval I j with respect to P n (there are at least ( 2π R − δ)n such intervals).…”
Section: Proof Of the Main Resultsmentioning
confidence: 99%
“…Another different aspect of our work is its universality, that the concentration phenomenon holds for many other ensembles where we clearly don't have invariance property at hands. One of the main ingredients is root repulsion, which has also been recently studied in various ensembles of random polynomials, see for instance [12,8,22,24] among others.…”
Section: Introductionmentioning
confidence: 99%
“…One way to measure randomness in the roots of a random polynomial is testing whether the polynomial has any double roots. For example, Tao and Vu [50] have shown that the spectrum of a random real symmetric n by n matrix with independent entries contains no double roots with probability tending to 1 as n increases (see also [18,41] for a related question on another class of random polynomials). For contrast, in the case of the characteristic polynomial of a random permutation matrix, the probability that the spectrum contains no double roots is the same as the probability of the permutation having only one cycle, which occurs with probability 1/n and tends to zero, rather than 1.…”
Section: Introductionmentioning
confidence: 99%